Determination of Employee Works Performance Through Employee Works Motivation With Organizational Support As An Moderating Variable At Pt. Meitech Eka Bintan - Kesuma, Endra Teja (Zona Manajerial: Program Studi Manajemen (S1), 2025)
This article Research was aimed to describe determination of Organizational culture, Employee competency, Employee commitment, Work environmental, Employee Works motivation, Organizational support, Employee work performances through Employee works motivation as an intervening variable and organizational supports as an moderating variable at PT. Meitech Eka Bintan (Oil and Gas Fabrication/Construction National Company) in Bintan Region, and also to understand the effect of direct connections between independent variables to intervening variable (employee works motivation) and indirect connecting between intervening variable (employee works motivation) to dependend variable (employee works perfomance) and influence of organizational support as an moderating variable which this variable might be having a negative influencing or positive influence for work motivation and/or employee works performance. This reseach use quesioner from a 30 respondens such as engineers, supervisors, craftmen and helper whom are existed on work site at PT. Meitech Eka Bintan. Data analytics to be using SPSS 31 version.